Toxic Metal Pollution Abatement Using Sour Orange Biomass - Abdul Sattar, Jwan A (Al-Nahrain Journal of Science, 2013)
In this work, Sour orange (SOR) peels waste was used as a solid adsorbent for removal of Cobalt (III) ions from aquatic ecosystem through batch techniques, the influence of biosorbent dose, initial concentration, temperature, contact time and pH on the Co (III) ions removal percentage were investigated. Optimum removal of Co(III) ions was achieved at biosorbent (2 gm),initial Co(III) ions (5 mg/l), temperature(30 Cº), contact time(90 min.) and pH(2). Desorption experiments were performed due to the importance for the financial competitiveness of biosorption with other process, indicating that (0.1 M) Ammonium chloride is the most promising desorbing agent for efficient sorbent regeneration. The adsorbent was characterized using FT-IR spectroscopy detecting the changes in hydroxyl and carboxyl groups before and after biosorption confirming their involvement in Co (III) ions binding. Various parts of SOR were selected for comparative studies on the Co (III) ions removal percentage indicating that SOR peels has the highest Co (III) ions removal percentage, followed by the other parts. Bioactivity inquires revealed that the SOR peels has a bioactivity against Pseudomonas aeruginosa. The results of this study confirm that SOR peels waste can be used beneficially in treating aquatic ecosystem containing Co (III) ions.